Grounded Theory for the Design of Mobile User Interfaces-Based on Space Retrieval Therapy - Aljedaani, Kholoud Abdulrahman; Alnanih, Reem Abdulaziz (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Technology plays a major role in our daily lives. In healthcare, technology assists in treating and detecting diseases and can improve patients’ quality of life. Alzheimer’s disease patients are generally elderly people who suffer from disabilities in vision, hearing, speech, and movement. The disease is one of the most common types of dementia. This paper proposes a design for a mobile application with an adaptive user interface for Alzheimer’s patients based on an elderly model developed using grounded theory. The application aims to improve the patients’ quality of life and allow them to remain engaged in society. The design of the application is based on spaced retrieval therapy (SRT), a method that helps Alzheimer’s patients to recall specific pieces of important information. User-centered design method was used to design and build this application. In the requirements phase, a user model for elderly people was elicited based on a classification developed through grounded theory. The prototype for the proposed model was designed and developed considering the default user interfaces and the adaptive user interfaces. A test was conducted with 15 elderly Arab users. The participants were 50–74 years old with varying levels of education and experience with technology. The authors proposed a user model for elderly people containing all the design implications in terms of physical and cognitive changes. The results of testing with elderly Arab users supported the proposed user model in terms of colors, fonts, pictures, and symbols. However, there were problems with the menu design and color preferences.